1993
DOI: 10.1073/pnas.90.18.8707
|View full text |Cite
|
Sign up to set email alerts
|

Release from quiescence of CD34+ CD38- human umbilical cord blood cells reveals their potentiality to engraft adults.

Abstract: Using optimal culture conditions in which the transforming growth factor 11 (TGF-j1) inhibitory loop has been interrupted by antiuense TGF-131 oligonudeotides or antf-TGF-1 serum, we have compared the proliferative capacities and the abUities ofthe CD34+ CD38-ceil populations from bone marrow and umbilical cord blood to generate early progenitors in long-term cultures. The CD34+ CD38-fraction of umbilical cord blood accounts for 4% of the CD34+ fraction compared to only 1% in bone marrow, indicating that umbil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
84
0
14

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(106 citation statements)
references
References 21 publications
8
84
0
14
Order By: Relevance
“…[9][10][11]21,26,27 Abrogation of autocrine or paracrine TGF-␤ with a neutralizing antibody or specific antisense oligonucleotides can improve the viability and proliferative potential of ex vivo cultured primitive hematopoietic cells. 9,11,21,[26][27][28][29] We have previously shown that true murine repopulating stem cell activity as measured by the quantitative murine competitive repopulation assay is also increased two-to four-fold by inclusion of neutralizing TGF-␤ antibody during culture in IL-3, IL-6 and SCF. 12 A number of potential mechanisms have been suggested for these inhibitory actions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11]21,26,27 Abrogation of autocrine or paracrine TGF-␤ with a neutralizing antibody or specific antisense oligonucleotides can improve the viability and proliferative potential of ex vivo cultured primitive hematopoietic cells. 9,11,21,[26][27][28][29] We have previously shown that true murine repopulating stem cell activity as measured by the quantitative murine competitive repopulation assay is also increased two-to four-fold by inclusion of neutralizing TGF-␤ antibody during culture in IL-3, IL-6 and SCF. 12 A number of potential mechanisms have been suggested for these inhibitory actions.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have also reported that abrogation of autocrine/paracrine TGF-␤ has beneficial effects on viability and proliferation of primitive hematopoietic cells. 8,[13][14][15][16] Diminution of TGF-␤ activity during ex vivo culture by neutralizing antibodies or antisense oligonucleotides has been shown to increase retroviral gene transfer efficiency into committed progenitor cells such as CFU-GEMM (colony-forming unit granulocyte-erythroid-megakaryocyte-macrophage). 17 However, assessment of gene transfer into committed progenitor cells is often not predictive of the efficiency of gene transfer into true repopulating stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Human umbilical cord blood, which contains hematopoietic stem/progenitor cells at a frequency equal to or greater than that of adult bone marrow (28,29), and with a high quality for proliferation (30)(31)(32)(33)(34) and self-renewal capacity, as estimated by replating colonies in vitro (30,31,35), has shown promise clinically as an alternative source of human transplantable and marrow-repopulating cells (36)(37)(38)(39)(40)(41)(42)(43). Hematopoietic stem and progenitor calls in human cord blood may be ideal targets as recipients of potential gene therapy for hematopoietic disorders (44).…”
mentioning
confidence: 99%
“…They are CD34 + /CD38 − , /Kit low , /Trf-R low , /FLT3 low , /Mpl low and /IL6-R low . 6,7,22 Interestingly, when CD34 + /Kit − , CD34 + /Kit low and CD34 + /Kit high cells were injected separately into preimmune fetal sheep recipients, only the CD34 + human marrow cells that express low levels of Kit protein, corresponding to the HPP-Q cells allowed a long-term engraftment. 24 Several in vivo models have been developed to test the ability of human stem cells to repopulate immune-deficient mice such as the NOD/SCID mice.…”
Section: Figure 2 Tgf-␤1 Mrna Is Expressed With a Higher Intensity Anmentioning
confidence: 99%
“…They provide larger mixed or GM colonies containing various hematopoietic lineages. [5][6][7] They respond to the inhibitory effect of very low endogenous concentrations of TGF-␤1. 10 In this study, we consider only the HPP-Q-Mix as they are the most primitive and could belong to the stem cell compartment.…”
mentioning
confidence: 99%